Hubungan Antara Self-Control dengan Perilaku Merokok pada Mahasiswa Universitas Negeri Padang - Syarif Ardiansyah; Adinda Yuniesya; Genta Prasetya; Reris Yumi Febriani; Surya Intan Putri Zai; Yodi Kasinda; Hanny Rufaidah Damra (Indo Publishing, 2026)
Smoking behavior among university students is one of the risky behaviors that can have negative impacts on both physical and psychological health. One of the psychological factors assumed to be associated with smoking behavior is self-control. This study aimed to examine the relationship between self-control and smoking behavior among students at Universitas Negeri Padang. This research employed a quantitative approach with a correlational design. The population consisted of active student smokers at Universitas Negeri Padang, with a sample of 33 respondents selected using a purposive sampling technique. Data were collected through questionnaires using the Self-Control Scale based on Averill's (1973) theory and the Smoking Behavior Scale based on Aritonang's (1997) dimensions. Data were analyzed using the Shapiro–Wilk normality test, linearity test, and Pearson Product Moment correlation with the assistance of SPSS software. The results indicated that the data were normally distributed; however, there was no significant relationship between self-control and smoking behavior. The Pearson correlation analysis yielded a correlation coefficient of r = 0.126 with a significance value of p = 0.486 (p > 0.05). Furthermore, the measure of association analysis revealed that self-control contributed only 1.6% to smoking behavior, while the remaining 98.4% was influenced by other factors beyond the scope of this study. Based on these findings, it can be concluded that there is no significant relationship between self-control and smoking behavior among students at Universitas Negeri Padang. Therefore, smoking behavior among university students is likely to be more strongly influenced by other factors, such as peer influence, social environment, smoking habits, and nicotine dependence.